Multivalent copper composite ozone catalyst with component gradient structure and preparation method thereof

By adopting a polyvalent copper composite ozone catalyst with a component gradient structure, a hydrothermal synthesis process is used to form a hydrated calcium silicate mineral with alkali-delivery function, which solves the reduction of catalyst active elements in the prior art during high-temperature calcination. Problem, high-efficiency ozone catalytic effect and long-life catalysts are achieved.

CN116966913BActive Publication Date: 2025-02-07NANJING UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311049172.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-07
Estimated Expiration
2043-08-21

AI Technical Summary

Technical Problem

During the high-temperature calcination process, existing ozone catalysts are prone to solid phase reaction between metal and support, resulting in a decrease in catalytic active elements.

Method used

Using a polyvalent copper composite ozone catalyst with a ingredient gradient structure, the active element grinding is prepared by mixing copper powder, copper oxide, copper sulfate, manganese dioxide and cerium oxide with concave and concave rod soil, dehydrated kaolin and other materials, and Hydrated calcium silicate minerals such as tobemullite and hard silicate are formed through hydrothermal synthesis, providing hydroxyl radicals and alkali-delivery calcium release functions.

Benefits of technology

The oxidation activity of the catalyst is improved, the ozone catalytic effect is enhanced, the service life of the catalyst is extended, and the treatment cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116966913B_ABST
    Figure CN116966913B_ABST
Patent Text Reader

Abstract

The present invention is a multivalent copper composite ozone catalyst with a composition gradient structure and a preparation method thereof. The steps include: (1) preparing active element ground material; mixing active components containing copper powder, copper oxide, copper sulfate, manganese dioxide and cerium oxide with attapulgite and dehydrated kaolin for ball milling; (2) preparing catalyst active shell layer mixture; (3) placing the dry core mixture into a mixer, adding water and stirring to form a wet mixture, and naturally homogenizing; (4) placing the naturally homogenized core mixture into a ball forming disk for rolling into balls, and the material forms a ball core; (5) adding the catalyst active shell layer mixture into the ball forming disk for multiple times to coat the active layer, forming a catalyst spherical body with a composition gradient; (6) curing. The catalyst prepared by the present invention has both an oxidized state and a reduced state, a large reaction interface, and retains the activity of the active elements, and has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heterogeneous ozone catalytic oxidation, and specifically relates to a multivalent copper composite ozone catalyst with a component gradient structure and a preparation method thereof. Background Art

[0002] Petroleum is a crude oil with high sulfur, high nitrogen, high carbon residue and high acid value. The wastewater and pollutants (carbon chain) discharged from petroleum refining and processing are high in content and poor in biodegradability. The refining wastewater in the production process is a kind of organic wastewater that is difficult to degrade. The pollutants in the wastewater mainly include petroleum hydrocarbons, volatile phenols, suspended solids, ammonia nitrogen and other toxic metal substances. The COD of the wastewater is high, and there are many difficult-to-degrade substances. Moreover, it is greatly affected by the alkalinity and acidity of the environment, and the pH value of the wastewater varies greatly. The wastewater discharge of petroleum refining enterprises is huge. The discharge of pollutants should be reduced, the recycling rate of water should be increased, and the effluent must be deeply treated. Advanced oxidation processes (AOPs) developed in recent years have unique effects in treating wastewater. AOPs have a strong oxidizing function of hydroxyl radicals (·OH). ·OH and organic pollutants will undergo a series of reactions such as electron transfer, bond breaking, substitution and addition. The organic pollutants contained in the wastewater will be directly mineralized or degraded into small molecules through chemical reactions. AOPs can improve the biodegradability of wastewater. When combined with biochemical treatment, it can reduce the treatment cost of refinery wastewater. It is the best choice for deep treatment of effluent and has broad application prospects.

[0003] As a practical and efficient advanced oxidation technology, ozone oxidation has the advantages of strong oxidation capacity, short reaction time, no secondary pollution, simple equipment, etc. Among them, heterogeneous ozone catalytic oxidation technology has great application value due to its advantages of high catalyst mechanical strength, low cost and easy recovery.

[0004] Currently, ozone catalysts often use supported metal catalysts, where transition metal elements are loaded in a porous ceramic matrix by impregnation in a solution, and then calcined at high temperature to obtain the catalyst. However, during the calcination process, solid-phase reactions between the metal and the carrier are easily generated, forming inactive metal oxides and compounds, and the metal is converted from an ionic state to a stable oxide or the catalytic activity of the metal is reduced. Therefore, high-temperature calcination is the main reason for the reduction of active elements in the catalyst. Summary of the invention

[0005] The present invention aims to provide a method for preparing a multivalent Cu by using metal copper powder, copper oxide, copper sulfate, manganese dioxide, cerium oxide and the like as active elements. x+ Method for highly efficient ozone catalyst.

[0006] The technical solution to achieve the purpose of the present invention is: a method for preparing a multivalent copper composite ozone catalyst with a gradient composition structure, comprising the following steps:

[0007] Step (1): preparing active element fine material; mixing active components including copper powder, copper oxide, copper sulfate, manganese dioxide and cerium oxide with attapulgite and dehydrated kaolin and subjecting them to ball milling to obtain active element fine material;

[0008] Step (2): preparing a catalyst active shell mixture; placing the ground active element prepared in step (1) and the lime, attapulgite, and dehydrated kaolin in the cementitious material into a mixer, adding water and stirring, then digesting in a digestion bin, adding the digested material and the cement in the cementitious material into the mixer for secondary stirring to obtain a catalyst active shell mixture;

[0009] Step (3): placing the core mixture in a dry state into a mixer, adding water accounting for 30% of the core mixture, stirring to form a wet mixture, and allowing the materials to stand naturally for natural homogenization;

[0010] Step (4): placing the naturally homogenized core mixture into a ball-forming plate and rolling it into balls, so that the material forms a ball core, and the particle size of the ball core is controlled to be 3-10 mm;

[0011] Step (5): adding the catalyst active shell mixture obtained in step (2) to the spheroidizing plate in step (4) in multiple portions to coat the active layer, with the mass ratio of the core mixture to the active shell mixture being 40-80%:20-60%, spraying atomized water until the active shell mixture is completely coated on the surface of the core sphere, thereby forming a catalyst spherical body with a composition gradient;

[0012] Step (6): curing the catalyst spherical body.

[0013] Furthermore, the composition of the active components in step (1) with attapulgite and dehydrated kaolin is as follows in percentage by mass: 2-5% metallic copper powder, 10-30% copper oxide, 5-10% copper sulfate, 10-20% manganese dioxide, 2-5% cerium oxide, 25% attapulgite and 25% dehydrated kaolin.

[0014] Furthermore, in step (1), the mixed ball milling fineness is required to be 400 mesh, and the number of particles with a diameter of less than 40 microns in the obtained active element fine material is greater than 90%.

[0015] Furthermore, in step (2), the mass fractions of the active element ground material, cement, lime, attapulgite and dehydrated kaolin are as follows: 40-60%: 5-10%: 10-15%: 5-25%: 5-25%;

[0016] During the stirring before digestion in step (2), water accounting for 15% of the mass fraction of the dry material in the mixer is added for mixing, and a mixed material is obtained after stirring for 2-3 minutes; the digestion time is 3.5-4.5 hours, and the digested mixed material is obtained when the lime is converted into calcium hydroxide; the secondary stirring time is 2-3 minutes.

[0017] Furthermore, the copper powder in step (1) has a purity of more than 85% Cu, a fineness of 80-400 mesh, and copper oxide, copper sulfate, manganese dioxide, and cerium oxide are of industrial purity level;

[0018] The cement in step (2) is 525 ordinary Portland cement;

[0019] The silicon oxide content of attapulgite is greater than 60%, and the fineness requirement is 200 mesh sieve residue ≤ 5%;

[0020] The silicon oxide content of dehydrated kaolin is ≥ 60%, the cation exchange capacity is ≥ 110 mg equivalent / 100g, and the fineness is required to be 200-250 mesh;

[0021] The lime used is fast or medium-speed lime, with effective calcium content ≥80%, fineness 100 mesh and sieve residue ≤20%.

[0022] Furthermore, the stirring time in step (3) is 2-3 minutes, and the natural homogenization and natural standing time is 10-30 minutes.

[0023] Furthermore, the core mixture is composed of cement, diatomaceous earth, quartz powder, and xonotlite in a mass ratio of 25% cement: 40% diatomaceous earth: 25% quartz powder: 10% xonotlite, wherein the diatomaceous earth and quartz powder are mixed and ball-milled after being measured, and the fineness meets the 300 mesh less than 5%;

[0024] Xonotlite is synthesized by dynamic method, with a specific surface area greater than 100m 2 / g, fineness greater than 300 mesh; cement is 525 ordinary Portland cement; diatomaceous earth silicon oxide content is greater than 85%; quartz powder silicon oxide content is greater than 95%.

[0025] Furthermore, the curing in step (6) is specifically as follows: the catalyst spherical green bodies are stacked in a storage bin for static curing, and water spraying for moisturizing curing is started after the cement has finally set or after being statically cured for 8 hours. After static curing for 24-48 hours, the green bodies are placed in an autoclave for hydrothermal synthesis, and the hydrothermal reaction is carried out for 8-10 hours under the conditions of saturated steam pressure of 0.9-1.5 MPa and curing temperature of 170-200° C., and the product is obtained by natural cooling.

[0026] A multivalent copper composite ozone catalyst with a component gradient structure is prepared by the above method.

[0027] Compared with the prior art, the present invention has the following significant advantages:

[0028] (1) The core of the present invention adopts a hydrothermal synthesis process to form hydrated calcium silicate minerals such as tobermorite, xonotlite, and CSH (B). The addition of xonotlite seeds to the raw materials provides an induction and acceleration effect for the formation of a composite mineral phase of tobermorite and xonotlite. Tobermorite and xonotlite have the function of providing alkali and releasing calcium, and can provide hydroxyl radicals ·OH for catalysis, thereby accelerating the ozone catalytic effect.

[0029] (2) The present invention uses Cu, Cu 2+ , Cu x+ , Mn 4+ 、Ce 4+ 、Ce x+ In the digestion process of the active shell mixture and the hydrothermal synthesis environment of the catalyst sphere, a variety of chemical reactions are involved: copper powder oxidation reaction, copper sulfate and calcium hydroxide precipitation reaction, etc., which make the active catalytic elements show different valence states with the reaction, showing both oxidized and reduced states. The interaction between ions provides conversion conditions for multiple valence states, providing more oxygen free radicals ·O and hydroxyl free radicals ·OH for the ozone catalytic reaction.

[0030] (3) The active shell of the present invention adopts a silicate hydrothermal synthesis system to form hydrated calcium silicate (xCaO·SiO2·nH2O, x≤1, n≥1) and tobermorite phase (5CaO·6SiO2·5H2O). The silicon-oxygen bonds of the hydrothermally synthesized calcium silicate contain a large number of hydroxyl groups, which have the function of supplying alkali and releasing calcium. The dehydrated kaolin contains silicon oxide and attapulgite to form aluminum tobermorite in the calcium-silicon reaction. The aluminum tobermorite has ion exchangeability, forming a multi-component synergistic ion exchange superposition effect, which promotes the multivalent Cu x+ (x=0, 1, 2, 3) ion release and exchange.

[0031] (4) The active shell layer of the present invention adopts porous siliceous materials such as attapulgite and dehydrated kaolin. Under hydrothermal conditions, calcium-silicon reaction forms hydrated calcium silicate gel and tobermorite in situ in the siliceous material. The hydration product inherits the pore structure characteristics of attapulgite and dehydrated kaolin, has porosity and large specific surface area, provides more reaction interfaces for the catalyst, and improves the catalytic effect.

[0032] (5) The active shell of the present invention uses lime as the calcium raw material and adopts a digestion process. In the digestion stage, copper sulfate is ionized to form Cu 2+ Ions and SO4 2- Ion, Cu 2+ The ions react with calcium hydroxide to form nano-scale copper hydroxide precipitates, and the nano-copper hydroxide improves the catalytic activity of the Cu-based catalyst.

[0033] (6) Copper powder and Cu 2+ Ions and nano copper hydroxide precipitation constitute a multivalent copper system. The present invention uses multivalent Cu and active elements such as Mn and Ce to synthesize a structural catalyst with a component gradient under hydrothermal conditions, retaining the catalytic activity of the active elements, so that the present invention has excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the production process of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0036] A multivalent Cu x+ The preparation method of the composite high-efficiency catalyst includes the preparation of active element grinding material, catalyst core mixture material, catalyst active shell mixture material, catalyst core molding and active shell coating to form a new ozone catalyst with composition gradient and structure gradient.

[0037] 3.1 Active element grinding material

[0038] The present invention adopts metal copper powder, copper oxide, copper sulfate, manganese dioxide, cerium oxide and the like as active elements, and mixes the active elements with attapulgite and dehydrated kaolin according to the ratio of 2-5% of metal copper powder: 10-30% of copper oxide: 5-10% of copper sulfate: 10-20% of manganese dioxide: 2-5% of cerium oxide: 25% of attapulgite: 25% of dehydrated kaolin. Then, the active elements, attapulgite and dehydrated kaolin are mixed and ball-milled, the fineness requirement is 400 mesh, the number of particles with a diameter less than 40 microns is greater than 90%, and the active element ground material is obtained.

[0039] 3.2 Preparation of catalyst active shell mixture

[0040] The active shell layer is composed of active element ground material and cementitious material. The cementitious material is composed of cement, lime, attapulgite and dehydrated kaolin. The components of the active element ground material and the cementitious material are measured according to the ratio of 40-60% of active element ground material: 5-10% of cement: 10-15% of lime: 5-25% of attapulgite: 5-25% of dehydrated kaolin. The measured active element ground material, lime, attapulgite and dehydrated kaolin are added into a mixer, and water accounting for 15% of the dry materials in the mixer is added for mixing. After 2-3 minutes of stirring, a mixed material is obtained. The mixed material is put into a digestion bin for lime digestion. The digestion is carried out for 4 hours, and the lime is converted into calcium hydroxide to obtain a digested mixture.

[0041] Then add the measured cement and digestion mixture and stir for a second time for 2-3 minutes to obtain the catalyst active shell mixture.

[0042] Catalyst active shell mixture material performance requirements: cement is 525 ordinary Portland cement; the silicon oxide content of attapulgite is greater than 60%, and the fineness requirement is 200 mesh sieve residue ≤5%; the silicon oxide content of dehydrated kaolin is ≥60%, the cation exchange capacity is ≥110 mg equivalent / 100g, and the fineness requirement is 200-250 mesh; the lime uses fast or medium digestion speed lime, the effective calcium content is ≥80%, the fineness is 100 mesh and the sieve residue is ≤20%; the copper powder Cu content is greater than 99%, and the fineness is 80-400 mesh; copper oxide, copper sulfate, manganese dioxide, and cerium oxide are industrial pure grades that meet product industry standards.

[0043] 3.3 Core mixture composition

[0044] Core mixture composition: The core is composed of cement, diatomaceous earth, quartz powder, and xonotlite in a mass ratio of 25% cement: 40% diatomaceous earth: 25% quartz powder: 10% xonotlite. The diatomaceous earth and quartz powder are mixed and ball-milled after being measured, and the fineness meets the 300 mesh size of less than 5%. Pre-wet mixing water accounting for 30% of the core dry material is added.

[0045] Core mixture material performance requirements: Xonotlite is synthesized by dynamic method, with a specific surface area greater than 100m 2 / g, fineness greater than 300 mesh; cement is 525 ordinary Portland cement; diatomaceous earth silicon oxide content is greater than 85%; quartz powder silicon oxide content is greater than 95%.

[0046] The dry material mass ratio of the catalyst core mixture to the active shell mixture is 40-80%:20-60%.

[0047] 3.4 Multivalent Cu x+ Catalyst preparation steps

[0048] Step 1: The catalyst active shell mixture material is composed of active element ground material and gelling material. First, prepare the active element ground material, measure the active components copper powder, copper oxide, copper sulfate, manganese dioxide, cerium oxide, etc., and then mix and grind the active components with attapulgite and dehydrated kaolin to obtain the active element ground material;

[0049] Step 2: Put the ground active elements and the measured cementitious materials such as lime, attapulgite and dehydrated kaolin into a mixer, add 15% water to the dry materials and stir for 2-3 minutes, then digest in a digestion bin for 4 hours, add the digested materials and the measured cement into the mixer and further mix for 2-3 minutes to obtain the catalyst active shell mixture.

[0050] Step 3: Put the dry core mixture into a mixer, add 30% water to the core mixture, and then stir for 2-3 minutes to make a wet mixture. The wet mixture should be uniform and loose. Leave it naturally for 10-30 minutes to allow the material to be naturally homogenized so that the moisture in the material can be further diffused to achieve uniform distribution of moisture in the material.

[0051] Step 4: Put the naturally homogenized core mixture into the ball-forming plate and roll it into balls. Spray atomized water appropriately to form ball cores. When all the core mixture forms ball cores, the particle size of the ball cores is controlled to be 3-10mm.

[0052] Step 5: According to the mass ratio of the core mixture to the active shell mixture of 40-80%:20-60%, the catalyst active shell mixture that has been prepared, lime-digested and secondary-stirred is added to the ball-forming plate in 1-4 times for active layer coating, and atomized water is sprayed appropriately until the active shell mixture is completely coated on the surface of the core ball core to form a catalyst spherical body with a component gradient;

[0053] The catalyst spherical bodies are stacked in a storage bin for static curing. After the cement is finally set or after being static for 8 hours, water spraying for moisturizing curing is started. After static curing for 24-48 hours, they are placed in an autoclave for hydrothermal synthesis. The hydrothermal reaction is carried out for 8-10 hours under the conditions of saturated steam pressure of 0.9-1.5MPa and curing temperature of 170-200°C, and the product is obtained by natural cooling.

[0054] For the sake of convenience, all embodiments of the present invention take 100kg of catalyst core mixture as the benchmark, including 25kg of cement, 40kg of diatomite, 25kg of quartz powder, and 10kg of xonotlite, wherein diatomite and quartz powder are mixed and ball-milled after being measured, and the fineness meets 300 mesh less than 5%. The proportion of the remaining materials is adjusted and calculated based on the core material 100kg and the provisions of the invention.

[0055] Example 1

[0056] The dry material mass ratio of the catalyst core mixture to the active shell mixture is 40%:60%, and the catalyst active shell mixture is 150kg.

[0057] The catalyst active shell mixture consists of active element ground material and gelling material in a ratio of 55%:45%, 82.5kg of active element ground material and 67.5kg of gelling material.

[0058] The active element ground material is according to the ratio of copper powder 2%, copper oxide 30%, copper sulfate 5%, manganese dioxide 10%, cerium oxide 3%, attapulgite 25%, and dehydrated kaolin 25%. 1.65kg of copper powder, 24.75kg of copper oxide, 4.125kg of copper sulfate, 8.25kg of manganese dioxide, 2.475kg of cerium oxide, 20.6kg of attapulgite, 20.6kg of dehydrated kaolin are weighed and mixed and ball milled. The fineness requirement is 400 mesh, and the number of particles with a diameter less than 40 microns is greater than 90%, to obtain 82.5kg of active element ground material.

[0059] The cementitious material is prepared according to the ratio of cement 5%: lime 15%: attapulgite 20%: dehydrated kaolin 5%. 7.5 kg of cement, 22.5 kg of lime, 30 kg of attapulgite and 7.5 kg of dehydrated kaolin are weighed to obtain 67.5 kg of cementitious material.

[0060] For detailed coordination, see the corresponding embodiment number in Table 5.

[0061] Step 1: Obtain 82.5 kg of active element ground material.

[0062] Step 2: Put 82.5kg of ground active elements, 22.5kg of lime, 30kg of attapulgite and 7.5kg of dehydrated kaolin in a mixer, add 21.4kg of water accounting for 15% of the dry materials and stir for 2-3 minutes, then put the stirred materials into a digestion bin for digestion for 4 hours, add the digested materials and 7.5kg of measured cement into the mixer for secondary stirring, and mix for 2-3 minutes to obtain the catalyst active shell mixture.

[0063] Step 3: First, put 100kg of core mixture and 30kg of pre-wet water into a mixer and stir for 2-3 minutes to make a wet mixture. The wet mixture should be uniform and loose. Leave it naturally for 10-30 minutes to allow the material to be naturally homogenized so that the moisture in the material can be further diffused to achieve uniform distribution of moisture in the material.

[0064] Step 4: Put the naturally homogenized core mixture into the ball-forming plate and roll it into balls. Spray atomized water appropriately to form ball cores. When all the core mixture forms ball cores, the particle size of the ball cores is controlled to be 3-10mm.

[0065] Step 5: Add the prepared catalyst active shell mixture that has been lime-digested and stirred twice into the spheroidizing plate in 1-4 portions for active layer coating, and spray atomized water appropriately until the active shell mixture is completely coated on the surface of the core ball, forming a catalyst spherical body with a component gradient;

[0066] The catalyst spherical bodies are stacked in a storage bin for static curing. After the cement is finally set or after being static for 8 hours, water spraying for moisturizing curing is started. After static curing for 24-48 hours, they are placed in an autoclave for hydrothermal synthesis. The hydrothermal reaction is carried out for 8-10 hours under the conditions of saturated steam pressure of 0.9-1.5MPa and curing temperature of 170-200°C, and the product is obtained by natural cooling.

[0067] The product cylinder pressure strength is 24MPa and the apparent density is 1560kg / m 3 , water absorption rate 34%, specific surface area 54.2m 2 / g.

[0068] Sodium acetate was used as an ozone oxidation marker (simulated sewage), and the test results are as follows:

[0069] Example 1 Effect data, catalyst dosage 400g

[0070]

[0071]

[0072] Example 2

[0073] The dry material mass ratio of the catalyst core mixture to the active shell mixture is 80%:20%. The catalyst active shell mixture is 25kg.

[0074] The catalyst active shell mixture consists of two parts: active element fine material and gelling material, with a ratio of 60%:40%, 15kg of active element fine material and 10kg of gelling material.

[0075] The active element ground material is according to the following ratio: copper powder 5%, copper oxide 20%, copper sulfate 10%, manganese dioxide 10%, cerium oxide 5%, attapulgite 25%, and dehydrated kaolin 25%. Weigh 0.75kg of copper powder, 3kg of copper oxide, 1.5kg of copper sulfate, 1.5kg of manganese dioxide, 0.75kg of cerium oxide, 3.75kg of attapulgite, and 3.75kg of dehydrated kaolin, mix and ball mill. The fineness requirement is 400 mesh, and the number of particles with a diameter less than 40 microns is greater than 90%, to obtain 15kg of active element ground material.

[0076] The cementitious material is prepared according to the ratio of cement 10%: lime 10%: attapulgite 15%: dehydrated kaolin 5%. 2.5 kg of cement, 2.5 kg of lime, 3.75 kg of attapulgite and 1.25 kg of dehydrated kaolin are weighed to obtain 10 kg of cementitious material.

[0077] For detailed coordination, see the corresponding embodiment number in Table 5.

[0078] Step 1: Obtain 15 kg of active element ground material.

[0079] Step 2: Put 15kg of ground active elements and 2.5kg of lime, 3.75kg of attapulgite and 1.25kg of dehydrated kaolin in the measured cementitious materials into a mixer, then add 3.375kg of water accounting for 15% of the dry materials and stir for 2-3 minutes. Then put the stirred materials into a digestion bin for digestion for 4 hours. Add the digested materials and 2.5kg of measured cement into the mixer for secondary stirring. Mix for 2-3 minutes to obtain the catalyst active shell mixture.

[0080] Step 3: First, put 100kg of core mixture and 30kg of pre-wet water into a mixer and stir for 2-3 minutes to make a wet mixture. The wet mixture should be uniform and loose. Leave it naturally for 10-30 minutes to allow the material to be naturally homogenized so that the moisture in the material can be further diffused to achieve uniform distribution of moisture in the material.

[0081] Step 4: Put the naturally homogenized core mixture into the ball-forming plate and roll it into balls. Spray atomized water appropriately to form ball cores. When all the core mixture forms ball cores, the particle size of the ball cores is controlled to be 3-10mm.

[0082] Step 5: Add the prepared catalyst active shell mixture that has been lime-digested and stirred twice into the spheroidizing plate in 1-4 portions for active layer coating, and spray atomized water appropriately until the active shell mixture is completely coated on the surface of the core ball, forming a catalyst spherical body with a component gradient;

[0083] The catalyst spherical bodies are stacked in a storage bin for static curing. After the cement is finally set or after being static for 8 hours, water spraying for moisturizing curing is started. After static curing for 24-48 hours, they are placed in an autoclave for hydrothermal synthesis. The hydrothermal reaction is carried out for 8-10 hours under the conditions of saturated steam pressure of 0.9-1.5MPa and curing temperature of 170-200°C, and the product is obtained by natural cooling.

[0084] The product cylinder pressure strength is 28MPa and the apparent density is 1582kg / m 3 , water absorption rate 32%, specific surface area 50.6m 2 / g.

[0085] Sodium acetate was used as an ozone oxidation marker (simulated sewage), and the test results are as follows:

[0086] Example 2 Effect data, catalyst dosage 400g

[0087] unit <![CDATA[O3]]> <![CDATA[Catalyst + O3]]> Configure water sample concentration mg / L 400 400 Simulated sewage volume L 3.2 3.2 <![CDATA[O2 flow rate]]> L / min 2 2 <![CDATA[O3 flow rate]]> mg / L 80 80 Ozone contact time min 60 60 Initial COD mg / L 397.28 397.28 Final COD mg / L 337.12 179.97 COD reduction rate % 15.14 74.7

[0088] Example 3

[0089] The dry material mass ratio of the catalyst core mixture to the active shell mixture is 50%:50%. The catalyst active shell mixture is 100kg.

[0090] The catalyst active shell mixture consists of active element ground material and gelling material in a ratio of 40%:60%, 40kg active element ground material and 60kg gelling material.

[0091] The active element ground material is according to the following ratio: copper powder 5%, copper oxide 10%, copper sulfate 10%, manganese dioxide 20%, cerium oxide 5%, attapulgite 25%, and dehydrated kaolin 25%. 2kg of copper powder, 4kg of copper oxide, 4kg of copper sulfate, 8kg of manganese dioxide, 2kg of cerium oxide, 10kg of attapulgite, 10kg of dehydrated kaolin are weighed and mixed and ball milled. The fineness requirement is 400 mesh, and the number of particles with a diameter less than 40 microns is greater than 90%, to obtain 40kg of active element ground material.

[0092] The cementitious material is in the proportion of cement 8%: lime 12%: attapulgite 15%: dehydrated kaolin 25%. 8 kg of cement, 12 kg of lime, 15 kg of attapulgite and 25 kg of dehydrated kaolin are weighed to obtain 60 kg of cementitious material.

[0093] For detailed coordination, see the corresponding embodiment number in Table 5.

[0094] Step 1: Obtain 40 kg of active element ground material.

[0095] Step 2: put 40kg of ground active elements and measured cementitious materials such as 12kg of lime, 15kg of attapulgite and 25kg of dehydrated kaolin into a mixer, add 13.8kg of water accounting for 15% of the dry materials and stir for 2-3 minutes, then put the stirred materials into a digestion bin for digestion for 4 hours, add the digested materials and 8kg of measured cement into the mixer for secondary stirring, and mix for 2-3 minutes to obtain the catalyst active shell mixture.

[0096] Step 3: First, put 100kg of core mixture and 30kg of pre-wet water into a mixer and stir for 2-3 minutes to make a wet mixture. The wet mixture should be uniform and loose. Leave it naturally for 10-30 minutes to allow the material to be naturally homogenized so that the moisture in the material can be further diffused to achieve uniform distribution of moisture in the material.

[0097] Step 4: Put the naturally homogenized core mixture into the ball-forming plate and roll it into balls. Spray atomized water appropriately to form ball cores. When all the core mixture forms ball cores, the particle size of the ball cores is controlled to be 3-10mm.

[0098] Step 5: Add the prepared catalyst active shell mixture that has been lime-digested and stirred twice into the spheroidizing plate in 1-4 portions for active layer coating, and spray atomized water appropriately until the active shell mixture is completely coated on the surface of the core ball, forming a catalyst spherical body with a component gradient;

[0099] The catalyst spherical bodies are stacked in a storage bin for static curing. After the cement is finally set or after being static for 8 hours, water spraying for moisturizing curing is started. After static curing for 24-48 hours, they are placed in an autoclave for hydrothermal synthesis. The hydrothermal reaction is carried out for 8-10 hours under the conditions of saturated steam pressure of 0.9-1.5MPa and curing temperature of 170-200°C, and the product is obtained by natural cooling.

[0100] The product has a cylinder pressure strength of 21MPa, an apparent density of 1490kg / m3, a water absorption rate of 37%, and a specific surface area of ​​51.6m 2 / g.

[0101] Sodium acetate was used as an ozone oxidation marker (simulated sewage), and the test results are as follows:

[0102] Example 3 Effect data, catalyst dosage 400g

[0103]

[0104]

[0105] Example 4

[0106] The dry material mass ratio of the catalyst core mixture to the active shell mixture is 60%:40%. The catalyst active shell mixture is 66.7 kg.

[0107] The catalyst active shell mixture consists of active element ground material and gelling material, with a ratio of 50%:50%, 33.35kg of active element ground material and 3.35kg of gelling material.

[0108] The active element ground material is according to the following ratio: copper powder 3.5%, copper oxide 20%, copper sulfate 7.5%, manganese dioxide 15%, cerium oxide 4%, attapulgite 25%, and dehydrated kaolin 25%. 1.17kg of copper powder, 6.67kg of copper oxide, 2.5kg of copper sulfate, 5kg of manganese dioxide, 1.33kg of cerium oxide, 8.34kg of attapulgite, 8.34kg of dehydrated kaolin are weighed and mixed and ball milled. The fineness requirement is 400 mesh, and the number of particles with a diameter less than 40 microns is greater than 90%, to obtain 33.35kg of active element ground material.

[0109] The cementitious material is prepared according to the ratio of cement 10%, lime 8%, attapulgite 25%, and dehydrated kaolin 7%. 6.67 kg of cement, 5.34 kg of lime, 16.67 kg of attapulgite, and 4.67 kg of dehydrated kaolin are weighed to obtain 33.35 kg of cementitious material.

[0110] For detailed coordination, see the corresponding embodiment number in Table 5.

[0111] Step 1: Obtain 33.35 kg of active element ground material.

[0112] Step 2: put 33.35kg of ground active elements and measured cementitious materials such as 5.34kg of lime, 16.67kg of attapulgite and 4.67kg of dehydrated kaolin into a mixer, add 9kg of water accounting for 15% of the dry materials and stir for 2-3 minutes, then put the stirred materials into a digestion bin for digestion for 4 hours, add the digested materials and the measured cement 6.67kg into the mixer for secondary stirring, and mix for 2-3 minutes to obtain the catalyst active shell mixture.

[0113] Step 3: First, put 100kg of core mixture and 30kg of pre-wet water into a mixer and stir for 2-3 minutes to make a wet mixture. The wet mixture should be uniform and loose. Leave it naturally for 10-30 minutes to allow the material to be naturally homogenized so that the moisture in the material can be further diffused to achieve uniform distribution of moisture in the material.

[0114] Step 4: Put the naturally homogenized core mixture into the ball-forming plate and roll it into balls. Spray atomized water appropriately to form ball cores. When all the core mixture forms ball cores, the particle size of the ball cores is controlled to be 3-10mm.

[0115] Step 5: Add the prepared catalyst active shell mixture that has been lime-digested and stirred twice into the spheroidizing plate in 1-4 portions for active layer coating, and spray atomized water appropriately until the active shell mixture is completely coated on the surface of the core ball, forming a catalyst spherical body with a component gradient;

[0116] The catalyst spherical bodies are stacked in a storage bin for static curing. After the cement is finally set or after being static for 8 hours, water spraying for moisturizing curing is started. After static curing for 24-48 hours, they are placed in an autoclave for hydrothermal synthesis. The hydrothermal reaction is carried out for 8-10 hours under the conditions of saturated steam pressure of 0.9-1.5MPa and curing temperature of 170-200°C, and the product is obtained by natural cooling.

[0117] The product cylinder pressure strength is 26MPa and the apparent density is 1496kg / m 3 , water absorption rate 38%, specific surface area 52.8m 2 / g.

[0118] Sodium acetate was used as an ozone oxidation marker (simulated sewage), and the test results are as follows:

[0119] Example 4 Effect data, catalyst dosage 400g

[0120] unit <![CDATA[O3]]> <![CDATA[Catalyst + O3]]> Configure water sample concentration mg / L 400 400 Simulated sewage volume L 3.2 3.2 <![CDATA[O2 flow rate]]> L / min 2 2 <![CDATA[O3 flow rate]]> mg / L 80 80 Ozone contact time min 60 60 Initial COD mg / L 397.28 397.28 Final COD mg / L 337.12 171.23 COD reduction rate % 15.14 76.9

[0121] Table 5 Calculation ratio (%) and weight (kg) of each implementation column based on 100 kg of core mixed material

[0122]

Claims

1. A method for preparing a multivalent copper composite ozone catalyst with a gradient composition structure, characterized in that: The steps include: Step (1): preparing active element fine material; mixing active components including copper powder, copper oxide, copper sulfate, manganese dioxide and cerium oxide with attapulgite and dehydrated kaolin and subjecting them to ball milling to obtain active element fine material; Step (2): preparing a catalyst active shell mixture; placing the ground active element prepared in step (1) and the lime, attapulgite, and dehydrated kaolin in the cementitious material into a mixer, adding water and stirring, then digesting in a digestion bin, adding the digested material and the cement in the cementitious material into the mixer for secondary stirring to obtain a catalyst active shell mixture; Step (3): placing the core mixture in a dry state into a mixer, adding water accounting for 30% of the core mixture, stirring to form a wet mixture, and allowing the materials to stand naturally for natural homogenization; The core mixture is composed of cement, diatomaceous earth, quartz powder, and xonotlite in a mass ratio of 25% cement: 40% diatomaceous earth: 25% quartz powder: 10% xonotlite, wherein the diatomaceous earth and quartz powder are mixed and ball-milled after being measured, and the fineness meets the requirement of less than 5% of 300 mesh; Xonotlite is synthesized by dynamic method, with a specific surface area greater than 100m 2 / g, fineness greater than 300 mesh; cement is 525 ordinary Portland cement; diatomaceous earth silicon oxide content greater than 85%; quartz powder silicon oxide content greater than 95%; Step (4): placing the naturally homogenized core mixture into a ball-forming plate and rolling it into balls, so that the material forms a ball core, and the particle size of the ball core is controlled to be 3-10 mm; Step (5): adding the catalyst active shell mixture obtained in step (2) to the spheroidizing plate in step (4) in multiple portions to coat the active layer, with the mass ratio of the core mixture to the active shell mixture being 40-80%:20-60%, spraying atomized water until the active shell mixture is completely coated on the surface of the core sphere, thereby forming a catalyst spherical body with a composition gradient; Step (6): Curing the catalyst spherical bodies: stacking the catalyst spherical bodies in a storage bin for static curing, spraying water for moisturizing curing after the cement has finally set or after being static for 8 hours, and placing them in an autoclave for hydrothermal synthesis after static curing for 24-48 hours, performing hydrothermal reaction at a saturated steam pressure of 0.9-1.5 MPa and a curing temperature of 170-200° C. for 8-10 hours, and cooling naturally to obtain the product.

2. The method according to claim 1, characterized in that The composition of each component in the active component in step (1) and attapulgite and dehydrated kaolin is as follows in mass percentage: 2-5% metallic copper powder, 10-30% copper oxide, 5-10% copper sulfate, 10-20% manganese dioxide, 2-5% cerium oxide, 25% attapulgite and 25% dehydrated kaolin.

3. The method according to claim 2, characterized in that The mixed ball milling fineness in step (1) is required to be 400 mesh, and the number of particles with a diameter of less than 40 microns in the obtained active element fine material is greater than 90%.

4. The method according to claim 3, characterized in that In step (2), the mass fractions of the active element ground material, cement, lime, attapulgite and dehydrated kaolin are as follows: 40-60%: 5-10%: 10-15%: 5-25%: 5-25%; During the stirring before digestion in step (2), water accounting for 15% of the mass fraction of the dry material in the mixer is added for mixing, and a mixed material is obtained after stirring for 2-3 minutes; the digestion time is 3.5-4.5 hours, and the digested mixed material is obtained when the lime is converted into calcium hydroxide; the secondary stirring time is 2-3 minutes.

5. The method according to claim 4, characterized in that The copper powder in step (1) has a purity of more than 85% and a fineness of 80-400 mesh, and copper oxide, copper sulfate, manganese dioxide and cerium oxide are of industrial purity level; The cement in step (2) is 525 ordinary Portland cement; The silicon oxide content of attapulgite is greater than 60%, and the fineness requirement is 200 mesh sieve residue ≤ 5%; The silicon oxide content of dehydrated kaolin is ≥ 60%, the cation exchange capacity is ≥ 110 mg equivalent / 100g, and the fineness is required to be 200-250 mesh; The lime used is fast or medium-speed lime, with effective calcium content ≥80%, fineness 100 mesh and sieve residue ≤20%.

6. The method according to claim 5, characterized in that The stirring time in step (3) is 2-3 minutes, and the natural homogenization and natural standing time is 10-30 minutes.

7. A multivalent copper composite ozone catalyst with a composition gradient structure, characterized in that: The method is prepared by any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method and device for degrading pollutants through ultraviolet catalytic wet oxidation

    CN101863526A

  • Copper-doped manganese dioxide catalyst and preparation method therefor

    CN105797741A